The role of corporate social responsibility and earning management in mediation of the effect of corporate governance on corporate performance - Hidah, Miftaqul; Sedana, Ida Bagus Panji (International research journal of management, IT and social sciences, 2021)
The purpose of this study is to analyze the role of corporate social responsibility and earning management in mediating the influence of corporate governance on corporate performance. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The sample used is 8 manufacturing companies that publish annual reports and sustainability reports for 2016-2019. This study uses path analysis technique with SPSS. The results of the study found that corporate governance has a positive effect on corporate performance, corporate social responsibility has a negative effect on corporate performance, corporate governance also has a positive effect on corporate social responsibility. So that corporate social responsibility is able to mediate the relationship of corporate governance to corporate performance. However, the research also found that corporate governance has no effect on earnings management, earnings management has no effect on corporate performance and earnings management is unable to mediate the relationship between corporate governance and corporate performance.